2017
DOI: 10.1111/codi.13786
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node yield in right colectomy for cancer: a comparison of open, laparoscopic and robotic approaches

Abstract: Aim Studies have demonstrated a relationship between lymph node (LN) yield and survival after colectomy for cancer. The impact of surgical technique on lymph node yield has not been well explored. Method This is a retrospective study of right colectomies (RC) for cancer at a single institution from 2012–2014. Exclusion criteria were previous colectomy, emergent and palliative operations. All data were collected by chart review. Primary outcomes were LN yield and the lymph node to length of surgical specimen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 30 publications
(31 reference statements)
4
43
0
Order By: Relevance
“…The mean lymph node retrieval in the BTU-cohort of 40.2 is superior to the range of levels reported for classic laparoscopic as well as for open techniques. The improved lymph node yield in robotic RC if compared to historic laparoscopic and open techniques is in accordance with other reports [29, 30]. Our levels of lymph node harvest were comparable to very recent early series of BTU-RRC [31].…”
Section: Discussionsupporting
confidence: 91%
“…The mean lymph node retrieval in the BTU-cohort of 40.2 is superior to the range of levels reported for classic laparoscopic as well as for open techniques. The improved lymph node yield in robotic RC if compared to historic laparoscopic and open techniques is in accordance with other reports [29, 30]. Our levels of lymph node harvest were comparable to very recent early series of BTU-RRC [31].…”
Section: Discussionsupporting
confidence: 91%
“…A similar retrospective study compared the costs of a single surgeon's first 50 robotic versus laparoscopic rectal resections. 58 The study also compared operative times and costs as a function of experience within the robotic group, separating the 50 cases into three phases: the initial learning curve (cases [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], competent period (cases 20-40), and experienced phase (cases 41-50). On average, the operative times and overall costs were significantly higher in the robotic group than in the laparoscopic group.…”
Section: Costs Of Robotic Colorectal Surgerymentioning
confidence: 99%
“…These findings supported the idea that robotic ''gateway'' procedures can be used to bypass the steep learning curve for minimally invasive rectal surgery. 8 In addition, in a recent study by Widmar et al 9 the authors retrospectively reviewed 181 open, 163 laparoscopic, and 119 robotic right colectomies performed at the Memorial Sloan Kettering Cancer Center in New York. They found that robotic right colectomy improves LN yield and the LN to length of surgical specimen ratio, which may reflect a better and more precise mesocolic excision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymph node yield in right colectomies for cancer: a comparison of open, laparoscopic and robotic approaches. Widmar M, Keskin M, Strombom P, Beltran P, Chow OS, Smith JJ, Nash GM, Shia J, Russell D, García‐Aguilar J …”
mentioning
confidence: 99%